Assimilating socio-economic perspective in designing crop sector technology interventions: A farmer participatory study on coconut sector in Kerala - Thamban, C.; Thomas, Lijo; Chandran, K. P.; Jayasekhar, S.; Rajesh, M. K.; Vijayan, Jesmi; Srinivasan, V.; Nair, K. M.; Anil Kumar, K. S. (Journal of Plantation Crops, 2020)
The economic viability of coconut farming in the state has witnessed a steady decline due to a complex interplay of several socio-economic, environmental and institutional factors. But the crop sustains the livelihood of a significant share of the population in the state. Equitable growth in agricultural sector of the state cannot be attained unless the fortunes of coconut farming sector are revived. A critical understanding of the production environment is very important in crafting appropriate strategies for the sector. This study is based on a detailed analysis of socio-economic profile of 180 coconut farmers in Kerala across five major agro-ecological units, collected using pre-tested structured questionnaire. The study draws on trends in relevant socio-economic trends to examine the reasons for the vicious cycle of low investment-low profits -low productivity. The study identified structural agrarian changes like low dependence on farm income, High share of non-farm income, high cost and non-availability of skilled labour, etc., as contributing factors to the extant situation. Based on the socio-economic profile of the coconut farmer and technical studies, soil nutrient management centric strategy was identified as the key element in reorienting coconut farming. The intervention strategy was designed as an alternative approach for reviving the economic viability of coconut farming. The initial results on farmer perception on impact of technology intervention, with direct and indirect links to several biological and socio-economic limiting factors, indicate significant improvement across several parameters influencing crop productivity. Assimilating the lessons from the operation of the intervention strategy, the study also outlines a roadmap for multiple institutional involvements for scaling up this strategy across the state.